Association of leg bias with bipedal speed and power in developing soccer players - Witkowski, Z.; Lipecki, K.; Lyakh, V. (Perceptual and Motor Skills, 2014)
The aim of this research was to determine whether there is any association between leg bias and bipedal locomotion in young male soccer players. 227 participants, members of a Polish football club, were tested. Leg dominancy and maximal specific power of each leg were recorded.